Shaping of geopolymer composites by 3D printing. (February 2021) - Archez, J.; Texier-Mandoki, N.; Bourbon, X.; Caron, J.F.; Rossignol, S.
Abstract: This work aims to shape a hollow cylinder with a geopolymer and an additive manufacturing process (3D printing) without organic additives. The formulation of a geopolymer composite using only mineral parts is proposed and the parameters of the 3D printing process were optimized. The mechanical properties, the microstructure, and the adhesion of the layers of the printing material were analysed and compared with the literature. The results showed that the geopolymer composite could be printed with the addition of small ratios of wollastonite, glass fibers, or non-reactive aluminosilicate and by modifying the printing speed. The stacking layers exhibited a good adhesion between them, avoiding the so-called "cold joints" effect, and the fibers are flow-oriented during the process. Some hollow cylinders are successfully printed with a flexural strength of 15 MPa. Highlights: Geopolymer composites were shaped by additive manufacturing (3D printing). The slump rate was reduced with the optimisation of the formulation. The layers exhibit a good adhesion and the fibers are oriented. A flexural strength of 15 MPa was obtained for the printed material. The mechanical properties are a bit higher than the values found in the literature.